Cover Picture: Hemin Catalyzed Dealkylative Intercepted [2, 3]‐Sigmatropic Rearrangement Reactions of Sulfonium Ylides with 2, 2, 2‐Trifluorodiazoethane (Adv. Synth. Catal. 10/2020). Issue 10 (8th April 2020) - Yan, Xiaojing; Li, Chang; Xu, Xiaofei; Zhao, Xiaoyong; Pan, Yuanjiang
Abstract : The inside cover picture, provided by Yuanjiang Pan and co‐workers, illustrates the selectivity associated with reported method: the hemin‐catalyzed, carbene‐mediated, dealkylative intercepted [2, 3]‐sigmatropic rearrangement reactions of allylic sulfides with in situ generated 2, 2, 2‐trifluorodiazoethane. The product of the classic [2, 3]‐sigmatropic rearrangement from the sulfonium ylide intermediate was not formed; instead the allyl group was lost and the 2, 2, 2‐trifluoroethyl sulfide was formed. This transformation distinguishes itself by the concise process, mild conditions and efficiency achieved with the help from the natural catalyst, hemin. Details of this work can be found in the full paper on pages 2005–2011 (X. Yan, C. Li, X. Xu, X. Zhao, Y. Pan, Adv. Synth. Catal . 2020, 362, 2005–2011; DOI: 10.1002/adsc.201901534 ).